THE ENHANCEMENT TODDLER’S APPETITE THROUGH ACUPRESSURE TUI NA - Hesty Widowati Widowati; Sri Mukhodim Faridah Hanum; Agus - Salim (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Difficulty consumption is the complaint of most parents when it comes to paediatricians. Difficult eating continuously results in decreased calorie intake needed so that it can affect the growth and development of children. Acupressure can be a non-pharmacological therapy choice for increasing a child's appetite. Acupressure is a form of physiotherapy by providing massage and stimulation at specific points on the body. The purpose of this study was to determine the effectiveness of acupressure therapy to increase appetite in infants aged 1-5 years. In this study used pre-experimental design with one group pre post-test approach. The variables in this study were acupressure therapy and appetite. Respondents are children aged 1 to 5 years. The treatment is acupressure therapy six times (every three days). The pretest is done before acupressure therapy with weight measurement and posttest weight measurement after surgery. Paired T Test tested analysis of the two data. The results of this study indicate a T-test correlation of 0.952 with a significance value of 0,000 where α = 5% = 0.005 so that 0,000 <0.005, which means that there is an influence of Tui Na acupressure on increasing toddlers' appetite based on weight gain. Keywords: Acupressure, Toddler’s appetite